Study guides

Q: What does x equal when x squared minus 17x equals 60?

Write your answer...

Submit

Related questions

6-y equals 17x = -11

actually,10x squared minus 17 equals 63 would come out to x equals the square root of 8.to work this out, you would first at 17 to both sides to get 10x squared alone.63 plus 17 equals 80. you now have 10x squared equals 80. then divide each side by ten to get x squared alone. 80 divided by 10 equals 8. now you have x squared equals eight. finally, to find x, you find the square root of each side. x squared's square root is x, and 8's square root is 2.82842712 but I'm assuming you only have to write out x=√8.but the other answer was a good try:)Improved Answer:-10x2-17x = 6310x2-17x-63 = 0When factored: (5x+9)(2x-7) = 0Therefore the roots of the quadratic equation are: x = -9/5 and x = 7/2

11

3x2 + 17x + c = 0, rearranging gives c = -3x2 - 17x

17x + 2y = 23 is the equation of a straight line with gradient -8.5 and intercept 11.5

(5x + 2)(x + 3)

39 - 17x = 12 Subtract 39 from both sides: -17x = -27 Divide both sides by -17: x = 27/17 = 1.5882...

-x=-2

Given ef is the midsegment of isosceles trapezoid abcd bc equals 17x ef equals 22.5x plus 9 and ad equals 30x plus 12 find ad?

3x3 - 10x = 17x divide by x to both sides3x2 - 10 = 17 add 10 to both sides3x2 = 27 divide by 3 to both sidesx2 = 9x = Â±âˆš9x = Â±3

221

-2x^2 + 17x - 35 = 0 = (-2x + 7)(x - 5) x =7/2 or 5

One.

17/12

3x-8=7x+10x 3x-8=17x -8 = 14x -4=7x -4/7

Divide both sides by 17 to get x alone. 17x/17 is x, and 9/17 is approximately 0.529411764705882, or as a fraction, 9/17. therefore, x=9/17.

I'm not sure this was notated correctly. As written, this is -11x plus or minus 18, which doesn't factor.

17x-3 = 14

12x-17x = -5

i got x = 1.35 12x+18=41-5x +5x 17x+18=41 -18 17x=23 /17 x=1.35

-4 = 17x so x = -4/17

-17/23 and the intercept is 25/23

4x2-17x-15) = 0 (4x+3)(x-5) = 0 Therefore: x = -3/4 or x = 5

17x - 8 = 3x + 16 Add 8 to each side: 17x = 3x + 24 Subtract 3x from each side: 14x = 24 ie 7x = 12 so x = One and five-sevenths

(5x - 11)(2x + 1) if the term in x is negative; (5x + 11)(2x - 1) if it's positive.